Legal protection for outsourced workers/laborers due to termination of employment during the contract period - Chamdani, Chamdani; Nasution, Krisnadi; Suhartono, Slamet; Hufron, Hufron (Technium Social Sciences Journal, 2022)
The enactment of Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021 raises legal problems in the form of conflicts of norms and has not reflected legal protection in the theory of legal objectives that are fair, certain, and beneficial. In the event of termination of employment for outsourced workers / laborers with a certain time work agreement within the contract period, Article 62 of Law Number 13 of 2003 concerning Manpower expressly requires the party who terminates the employment relationship within the contract period to providing compensation in the amount of workers/ laborers’ wages until the deadline for the expiration of the term of the employment agreement, while in Article 61A of Law Number 11 of 2020 concerning Job Creation requires employers to provide compensation money whose amount is calculated based on the period of a certain time work agreement that has been implemented by the Worker/Labor. The problem in this study is how legal protection for outsourced workers / laborers due to Termination of Employment in the contract period and what is the concept of legal protection for outsourced workers / laborers due to Termination of Employment in the contract period. This research is a normative juridical research, namely research that examines the study of documents, namely using various legal materials such as: legislation, legal theory, case studies, court decisions and in the form of opinions of scholars (doctrine). The problem approach used in this study, using a statutory approach (Statute approach), conceptual approach (Conceptual approach), philosophical approach (Philosophical approach) and comparative approach (comparative approach) in different countries. In this study, the theory of the welfare state and the theory of legal protection as an analysis knife against the formulation of the first problem, while the theory of legal objectives and the theory of agreements as an analysis knife against the formulation of the second problem. From the results of this study, it was concluded that the legal protection for outsourced workers / workers due to termination of work in the contract period is not optimal and conflicts with each other because in Article 62 of Law Number 13 of 2003 concerning Manpower only provides compensation money in the amount of workers / laborers’ wages with a certain time work agreement until the deadline for the expiration of the term of the employment agreement (the remaining contract period), while in Article 61A of Law Number 11 of 2020 concerning Job Creation requires employers to provide compensation money whose amount is calculated based on the period of a certain time work agreement that has been implemented by the worker / laborer (the contract period that has been lived), s It does not cause legal uncertainty that leads to injustice for both outsourcing service providers and outsourced workers/laborers. In addition, normatively as stipulated in Law Number 13 of 2003 concerning Manpower, Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021. The concept of legal protection for outsourced workers/laborers due to termination of employment in the contract period , among others, can be implemented with an employment agreement between workers/laborers and outsourcing companies on the basis of an indefinite time work agreement, but if the work agreement between the worker/laborer and the outsourcing company on the basis of an indefinite time work agreement then the principle of transfer of protection for workers / laborers must be applied in the event that the employer company appoints a new outsourcing company and the new outsourcing company is obliged to accept the transfer of workers/laborers from the old outsourcing company, whose object of work remains and the previously existing work agreement must be continued without changing the existing provisions in the agreement, unless changes are made to increase profits for their workers/laborers due to increased experience and length of service. Then it is necessary to form special institutions such as in the UK, ACAS (Advisory, Concilitation and Arbitration Service) who become supervisors in the field of labor so that when there is a violation committed by the company to outsourced workers / laborers, through the ACAS institution can provide fair protection to outsourced workers/laborers and in the event of termination of employment of outsourced workers / laborers, the Industrial Relations Court can decide as an unlawful act and the outsourcing company must find a job replacement for the outsourced workers/laborers who experience termination during the contract period and who are notable need to establish a special Law regulating outsourcing.